A Process for Defining Relations between Urban Integration and Residential Market Prices. (10th June 2016) - Giannopoulou, Maria; Vavatsikos, Athanasios P.; Lykostratis, Konstantinos
Abstract: The relationship between urban land value and accessibility has long been recognized. Location attractiveness can have a significant impact on growth of areas with increased accessibility, both in spatial and economic terms. Space Syntax is a well - known methodology of urban analysis, which uses computer techniques to analyze urban configuration. In order to study space as a primary unit of analysis, space syntax has developed different spatial metrics. The research presented herein focuses on one of the most widespread of those metrics, integration, and how this parameter is related to urban values. The existing literature in the field of urban morphology supports considerably one of the theory's principal premises; that spatial accessibility is correlated with economic land use values. Focusing on the residential property market, real estate market transactions should be considered as spatially related phenomena and thus spatial analysis procedures are needed so as to examine and obtain relations during the valuation process. The proposed methodological approach, attempts to investigate the relation between residential market prices and global integration syntactic metric in Xanthi, a medium - sized city in Northern Greece, by comparing continuous surfaces of both variables using a combination of Space Syntax theory and Geostatistical models, as well as Geographical Information Technology (GIS).